An in‐needle solid‐phase microextraction device packed with etched steel wires for polycyclic aromatic hydrocarbons enrichment in water samples. Issue 9 (26th March 2019) - Yang, Ying; Mai, Weimei; Gao, Jingyi; Hu, Zhe; Xu, Jianqiao; Zou, Shichun
Abstract: A novel, low‐cost and effective in‐needle solid‐phase microextraction device was developed for the enrichment of trace polycyclic aromatic hydrocarbons in water samples. The in‐needle solid‐phase microextraction device could be easily assembled by inserting hydrofluoric acid‐etched wires, which were used as adsorbent, into a 22‐gauge needle tube within spring supporters. Compared with the commercial solid‐phase microextraction fiber, the developed device has higher efficiency for the extraction of polycyclic aromatic hydrocarbons with four to six rings from water samples using the optimized extraction conditions. With gas chromatography equipped with a flame ionization detector, the limits of detection for the polycyclic aromatic hydrocarbons with four to six rings ranged from 0.0020 to 0.0067 ng/mL. The relative standard deviations for one needle and needle‐to‐needle extractions were in the range of 5.2–9.9% ( n  = 5) and 3.4–12.3% ( n  = 5), respectively. The spiked recoveries of the polycyclic aromatic hydrocarbons in tap water samples ranged from 73.2 to 95.4%. This in‐needle solid‐phase microextraction device could be a good field sampler because of the low sample loss over a long storage time.